Sanitasi Lingkungan Kerja Industri Roti A di Yogyakarta - Lina Hanarisanty; Kurniati Kurniati; Rivara Syara Nasution (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Universal, 2023)
Environmental sanitation plays an important role in increasing the degree of health in the world. One of the applications of sanitation is in the industrial world known as work environment sanitation. Sanitation in the work environment needs to be done so that workers are protected from disease. In addition, workers will feel safe and comfortable when working if the available sanitation meets the requirements. Observations were made in the Yogyakarta City Bread Industry to see the sanitary conditions of the work environment in the industry. The purpose of this research is to observe sanitation conditions regarding the Regulation of the Minister of Industry of the Republic of Indonesia No. 75/M-IND/PER/7/2010. The method used is direct observation in the industry using a checklist form and supporting data such as noise, lighting, temperature and humidity. The results of the analysis found that the sanitation of the work environment for bakery industry A in Yogyakarta City did not meet the requirements.